Rediscovery of a halophytic endemic and rare species of Portulaca (Portulacaceae) from central Argentina: morphology and its phylogenetic position - Cantero, Juan Jose; Barboza, Gloria E.; Ocampo, Gilberto (Phytotaxa, 2017)
Portulaca ragonesei (Portulacaceae), an extreme holophyte species from Salina de Ambargasta, central Argentina, is here illustrated and re-described based on morphological evidence. In addition, molecular data shows that this endemic species is one of the earliest-divergent lineages of the Oleracea clade. This is a critically endangered species that can be morphologically distinguished by its sprouting geophytes habit, the linear leaves, and the presence of constriction at the apex of the pixidium where only one seed is found.